Motivasi Kerja Guru Dalam Perspektif Islam: Analisis Teoritis Terhadap Teori Motivasi Modern - Hamidah, Dewi Tsalitsul; Ali, Moh; Cahyani, Dewi (Universitas Pakuan, 2025)
TEACHER WORK MOTIVATION FROM AN ISLAMIC PERSPECTIVE: A THEORETICAL ANALYSIS OF MODERN MOTIVATION THEORY Teacher work motivation is an essential factor in improving performance and the effectiveness of the educational process. This study aims to analyze the concept of work motivation from an Islamic perspective and compare it with modern motivation theories such as Maslow’s hierarchy of needs, Herzberg’s two-factor theory, and McClelland’s needs theory. This research employs a library research method by examining various relevant literature, both from classical Islamic sources and modern management theories. The findings show that motivation in Islam is rooted in spiritual values such as intention, sincerity, trustworthiness, and an orientation toward the Hereafter, which provide a transcendental dimension to teachers’ work behavior. Meanwhile, modern motivation theories tend to focus on the fulfillment of worldly needs such as salary, recognition, and achievement. Integrating both approaches results in a comprehensive Islamic work motivation model-one that encourages teachers to work professionally while maintaining an orientation toward worship. Thus, managing teacher work motivation based on Islamic values becomes an important strategy for improving the quality and work ethic of educators in Islamic educational institutions